Optimizing Employee Success Through Quality, Professionalism, and Commitment: Mengoptimalkan Kesuksesan Karyawan Melalui Kualitas, Profesionalisme, dan Komitmen - Tiara Ramadhani; Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the combined impact of human resource quality, work professionalism, and commitment on employee performance at PT. Mitra Jua Abadi in Waru-Sidoarjo. Utilizing a quantitative approach and saturated sampling technique, data was collected from 40 employees through Likert-scale questionnaires and analyzed using SPSS version 25. The findings reveal a significant collective influence of human resource quality, work professionalism, and commitment on employee performance. These results underscore the importance of enhancing human resource quality and fostering work professionalism and commitment within the organization to ensure sustained success and improved employee performance. Highlights: Examining employee factors. Data analyzed from 40 employees. Impacts on organizational success. Keywords: Employee Performance, Human Resource Quality, Work Professionalism, Commitment, Organizational Success